2021
DOI: 10.1590/1678-4499.20200492
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting rhizobacteria effect on maize growth and microbial biomass in a chromium-contaminated soil

Abstract: Chromium contamination in soils affects plant growth and this metal can accumulate in plants tissues. In addition, Cr can affect soil microbial biomass and activity. On the other hand, plant growth-promoting rhizobacteria (PGPR) can protect plants against metals and, at the same time, promote plant growth and could alleviate adverse effects on microbial biomass. This study evaluated five PGPR on maize growth, Cr accumulation and soil microbial biomass in a Cr-contaminated soil. Five PGPR (LCC04, LCC41, LCC69, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Fan et al [ 53 ] reported that the expression of genes involved in the formation of biofilms was enhanced by maize root exudates. Silva et al [ 54 ] reported that the inoculation of Z. mays with some PGPR strains reduced the accumulation of Cr in Z. mays , and this reduction in the accumulation of Cr may be due to the reduction of the mobile Cr 6+ to the immobile toxic Cr 3+ ions, as reported by Jing et al [ 13 ]. This agrees with the results of our study and suggests that reductions in the oxidation states of element ions in the soil, which lead to element immobilization and reduced bioavailability, might be the reason for the reduced uptake of some elements upon inoculation with PGPR.…”
Section: Discussionmentioning
confidence: 86%
“…Fan et al [ 53 ] reported that the expression of genes involved in the formation of biofilms was enhanced by maize root exudates. Silva et al [ 54 ] reported that the inoculation of Z. mays with some PGPR strains reduced the accumulation of Cr in Z. mays , and this reduction in the accumulation of Cr may be due to the reduction of the mobile Cr 6+ to the immobile toxic Cr 3+ ions, as reported by Jing et al [ 13 ]. This agrees with the results of our study and suggests that reductions in the oxidation states of element ions in the soil, which lead to element immobilization and reduced bioavailability, might be the reason for the reduced uptake of some elements upon inoculation with PGPR.…”
Section: Discussionmentioning
confidence: 86%